Optimization of Substrate Layer Material and Its Mechanical Properties for Piezoelectric Cantilever Energy Harvesting System. Issue 8 (8th July 2021) - Kumar, Akash; Singh, Jagpreet
Abstract: A cantilever piezoelectric energy harvester (PEH) is a popular choice to harvest energy for applications with natural or unnatural vibrations. Other than the choice of piezoelectric material, the substrate layer material also plays an important role to increase the energy harvesting in PEH. Earlier researches have emphasized on selecting a few substrate materials than all available in literature. However, we argue that the choice of the substrate material and its mechanical properties depend on the design of the PEH. We establish this fact by designing 20 different PEH models by varying the size of cantilever, substrate layer thickness, and types of the piezoelectric materials. These models are simulated in COMSOL with every known substrate material to select the best substrate material. We also propose a greedy approach to further increase the energy harvesting by optimizing the mechanical properties of the best substrate material. In all models, the best substrate material harvests at least 2 × more energy. The greedy approach increases energy harvesting in almost 50% of the models. Some of the substrate materials with optimized mechanical properties are reported in literature, however, this research opens up a discussion to manufacture new substrate materials to increase energy harvesting in PEH. Abstract : This paper argues that the choice of the substrate material and its mechanical properties to increase the energy harvesting depend on the design of the piezoelectric cantilever energy harvester (PEH). In an extensive simulation study on COMSOL with 20 different PEH models, with proposed approach, the best substrate material has obtained a minimum of 2× improvement in energy harvesting.